The mediating effect of school conditions on the relationship between transformational leadership and teachers' commitment to change - Mohd Zawawi, Zakaria (2015)
The purpose of this study is to examine the relationship between transformational leadership and teachers’ commitment to change. This study also examines if school conditions as a mediator impact transformational leadership and teachers’ commitment to change among secondary school teachers in Perlis. To attain the objectives, the quantitative method was used and data were collected through survey among secondary school teachers in Perlis. A total of 322 questionnaires were distributed and 254 questionnaires were returned which constituted 78% response rate. However 2 questionnaires were incomplete. Thus, only 252 questionnaires were used for further analysis. The study utilized reliability analysis, descriptive statistics, factor analysis, pearson correlation, and regression to examine the relationship between variables. The results revealed that transformational leadership was significantly related to teachers’ commitment to change and school conditions mediate the relationship between transformational leadership and teacher’s commitment to change. Future research needs to include other factors that influence commitment to change such as instructional leadership and training